2011
DOI: 10.1002/esp.2224
|View full text |Cite
|
Sign up to set email alerts
|

Transport and storage of bed material in a gravel‐bed channel during episodes of aggradation and degradation: a field and flume study

Abstract: The dynamics of sediment transport capacity in gravel-bed rivers is critical to understanding the formation and preservation of fluvial landforms and formulating sediment-routing models in drainage systems. We examine transport-storage relations during cycles of aggradation and degradation by augmenting observations of three events of channel aggradation and degradation in Cuneo Creek, a steep (3%) gravel-bed channel in northern California, with measurements from a series of flume runs modeling those events. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 41 publications
4
58
0
Order By: Relevance
“…Instead, comparison with theoretical and flume-based observations of Lisle et al (2001) indicated that the sediment wave demonstrated dispersive properties. The patterns that we observed-pool filling, bed aggradation followed by degradation and incision, temporarily increased braiding, and bed sediment fining-are all consistent with sediment-wave dispersion (e.g., Lisle et al, 2001;Cui and Parker, 2005;Lisle, 2008;Pryor et al, 2011). The dominantly dispersive wave behavior (cf.…”
Section: Tablesupporting
confidence: 69%
See 1 more Smart Citation
“…Instead, comparison with theoretical and flume-based observations of Lisle et al (2001) indicated that the sediment wave demonstrated dispersive properties. The patterns that we observed-pool filling, bed aggradation followed by degradation and incision, temporarily increased braiding, and bed sediment fining-are all consistent with sediment-wave dispersion (e.g., Lisle et al, 2001;Cui and Parker, 2005;Lisle, 2008;Pryor et al, 2011). The dominantly dispersive wave behavior (cf.…”
Section: Tablesupporting
confidence: 69%
“…Well-controlled laboratory and flume investigations provide valuable steps toward understanding how sediment-supply pulses affect processes such as stream-channel evolution, bar formation, and avulsion (e.g., Lisle et al, 1997;Braudrick et al, 2009;Madej et al, 2009;Tal and Paola, 2010;Pryor et al, 2011); and modeling studies allow simulated manipulation of landscapes over a range of scales (e.g., Cui and Parker, 2005;Jerolmack and Paola, 2007;Karssenberg and Bridge, 2008;Wang et al, 2011). However, opportunities to study landscape response to major sediment influx over large field scales are much rarer and usually are not anticipated in advance (e.g., dam failure, volcanic eruptions, landslides, or debris flows; Meyer and Martinson, 1989;Montgomery et al, 1999;Hoffman and Gabet, 2007;Casalbore et al, 2011;Gran, 2012;Guthrie et al, 2012;Pierson and Major, 2014;Tullos and Wang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the positive relationships shown in some series in Figure 11 also lend support to the theory of morphology-driven variability in habitat. While results from a single catchment are presented, the episodic sediment supply regime and characteristics of channel response in Carnation Creek are not unique, and have been widely observed in other channel networks with varying degrees of hillslope-channel coupling (Madej and Ozaki, 1996;Sutherland et al, 2002;Hoffman and Gabet, 2007;Pryor et al, 2011). For example, Frissell et al (1986) states how landslides might impact channels at the reach-scale through altering sediment storage units, while Montgomery (1999) attempts to connect geomorphic process domains to disruption of the River Continuum Concept (Vannote et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Process. Changes in sediment loads from debris flows are common in mountain landscapes, and have also been shown to influence bar and pool characteristics downstream (Madej and Ozaki, 1996;Hoffman and Gabet, 2007;Pryor et al, 2011). Previous research highlights the connection between channel morphology and topography and larger-scale sediment supply dynamics, such as those imposed by channel-hillslope coupling (Hoffman and Gabet, 2007;Hassan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation